Corporate Social Disclosure (CSD) in annual reports of Singapore companies. - Chiang, Josephine Jia Yu. (2010)
Over recent years, there has been increasing focus and discussion in the corporate world regarding issues such as the triple bottom line, corporate social responsibility (CSR) and corporate social disclosures (CSD) by companies. Corporations are no longer seen as stand-alone entities with solely profit-making goals, but as corporate citizens with responsibilities to not only engage in socially responsible activities, but also to communicate what they have done with their various stakeholders and the community as a whole. Corporate Social Disclosures (CSD) serves as a means of letting society know that they are committed to being socially responsible, but it has been found that different companies engage in CSD to different extents.